y squared-y-72 is an algebraic expression because it does not contain an equality sign.
xsquared minus x minus 72
y squared minus 9 (y*y)- 9 cannot be solved because there is no given value for 9.
y² - y - 6 = (y + 2)(y - 3)
72 minus the root of squared minus equals 72 but you have to be smart to know that the minimum circumference s 56 there you go
You have to put your heart into it!
There are no rational factors.
The factoring is as follows: x2 - y2 = (x + y) * (x - y)
it depends,if y = 0 the answer is -12 if y = 5 then the answer is 368
it is (x-y)(x-y) :)
y2-4y-32 = (y+4)(y-8) when factored
(7x + 8)(7x - 9)
2y(y + 3)(y - 7)
x^2 - y^2 - 4 is in its simplest form.
It is not clear what you want to solve for.
(y - 2)(y - 7)
(y - 8)(y - 2)
9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)
The answer? There is no "answer" There cannot be an answer because they are all different. In order to make calculations, the variables have to be the same. x squared, xy, y squared are the variables, and none of them match. Therefore your "answer" must look like this: 9x squared - 6xy + y squared - 81. Hope I Helped :D
9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)
4(y - 3)(y + 3)